Audit committee chair accounting expertise and audit report timeliness: The moderating effect of chair characteristics. Issue 2 (7th May 2019) - Baatwah, Saeed Rabea; Salleh, Zalailah; Stewart, Jenny
Abstract : Purpose: The purpose of this paper is to investigate whether the characteristics of the audit committee (AC) chair affect audit report timeliness. In particular, the direct association between AC chair accounting expertise and audit report delay, and the moderating effect of other characteristics of AC chair on this association are examined. Design/methodology/approach: To achieve the purpose of this study, the characteristics examined by this study are AC chair expertise, shareholding, tenure and multiple directorships. Furthermore, a sample of Malaysian companies during the period 2005–2011 and the fixed effects panel data method are utilized. Findings: The results suggest that an AC chair with accounting expertise is associated with a reduction in audit delay. The reduction is more obvious when the chair holds shares in the company, but is weakened by longer tenure and multiple directorships. These results are robust after conducting several robust tests. Using mediating analysis, the authors also document that an AC chair with accounting expertise can enhance the timeliness of audit reports even when the quality of financial reporting is lower. The reported result is supported by additional analysis that finds that AC chairs with accounting expertise and AC chairs with accounting expertise and shareholding are significantly associated with shorter abnormal audit delay. Originality/value: This study provides comprehensive analysis concerning the association between AC chair and audit report timeliness using a unique setting. It is among the limited evidence that reports the moderating effect of AC chair characteristics on the role of such chair on audit report timeliness.